Discrimination of Uranotaenia species (Diptera: Culicidae) from Madagascar based on morphology and wing morphometric traits - Tantely, Michaël Luciano; Randrianambinintsoa, Fano Jose; Rakotonirina, Antsa; Woog, Friederike; Boyer, Sebastien; Girod, Romain (Zootaxa, 2020)
The genus Uranotaenia (Diptera: Culicidae) has been well documented in Madagascar where it includes 73 species, 89.4% being endemic. However, one problem is that most species are morphologically similar in the adult stage. Here, 713 Uranotaenia specimens collected in the tropical forests of Anorana and Maromizaha between 2008 and 2014 were examined. Using the dichotomous keys for the Uranotaenia fauna of Madagascar published in 2004, three species were identified: Uranotaenia neireti (220), Ur. alboabdominalis (110) and Ur. mayottensis (28). The other specimens (355) were not identifiable and were classified as Uranotaenia sp1. Using wing morphometry, the four taxa were classified into four morphogroups. Within the Uranotaenia sp1 group, specimens from the Anorana forest and those from the Maromizaha forest overlapped. This result suggests that wing morphometric traits could be a good marker to distinguish Uranotaenia species in Madagascar.